Clause Combining in Ancient Greek Narrative Discourse : the Distribution of Subclauses and Participial Clauses in Xenophon's Hellenica and Anabasis. - Buijs, Michel (Mnemosyne : Bibliotheca Classica Batava Ser. ;, 2004)
This study describes the usage of subclauses and participial clauses in Xenophon's Hellenica and Anabasis, with additional examples from other texts by Xenophon, providing new insights into the distribution of these clauses by adopting a text grammar-oriented approach.